EVALUASI IMPLEMENTASI KEBIJAKAN PERSALINAN BAGI MASYARAKAT MISKIN OLEH BIDAN PRAKTEK SWASTA DI KOTA TANJUNGPINANG - Mubasysyir Hasanbasri, Elfrida Tambun (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Economy factor is one of the factors that couldhampered communityâs access in the utilization of health service.To guarantee effort of poor community access towardhealth service, the government was conducted managed program.The limitation of working hours in primary health carewas causing limited service hours. Therefore, in order to solvethe problem, the government stated that private midwife practiceas one of the health services could be utilized by poorcommunity with budget that was covered by government. Thegovernmentâs policy has not yet able to improve the coverageof delivery attendant by health care provider. Hence, an evaluationto find out the phenomenon occurred in the community isnecessary to solve this problem in order to improve the healthservice in the future.Objective : This research was aimed to find out the descriptionof delivery care for poor community by private midwife inTanjungpinang Municipality.Method: This was a descriptive research that used qualitativeapproach with case study design. The research subjectwas civil servant midwife who had midwifery private practice,head of primary health care, head of health office, headof family health division, and mothers who delivered and hadaskeskin (health insurance for poor community) card. Theselection for midwife and mothers who delivered was usingpurposive sampling technique. Furthermore, the data wascollected by using primary data that was obtained from indepthinterview result that used interview guidance, while the secondarydata was obtained from document observation, andthe data will be analysed qualitatively.Result: The policy of delivery for poor community inTanjungpinang Municipality has not yet obtained optimalsupport.The limited bugdet availability affected in a way thatnot all of the midwives were willing to assist askeskin patientwith cost claim to primary health care. Private practice midwifeasked for fee from askeskin patient. There was no differencethe treatment given between askeskin patient and private/paying patient. However, askeskin patient was satisfiedwith the service given by private practice midwife.Conclusion: The implementation of delivery policy for poorcommunity by private practice midwife has not yet optimal asthere was a lack of support from municipality government,administratively or financially.Keyword: Evaluation, policy implementation, private midwifepractice and poor community